Development of Image Media Using Flannel Cloth on Learning Outcomes of Class IV Primary School Students on Natural Science Materials (IPA) - Aulia Putri, Rani; Fitriyani, Rini; Ramadhani Lubis, Renni (International Journal of Students Education, 2024)
The use of learning media in conveying natural science (science) material to fourth grade elementary school children is very necessary for teachers so that children become interested and happy, so that it will generate motivation in learning and curiosity in fourth grade elementary school children. The aim of this research is to determine the development of flannel board media to improve learning outcomes for fourth grade elementary school children. Types of development research (research and development). The development procedure according to 4D theory consists of four stages, 4D model consisting of define, design, develop, disseminate. After being carried out using flannel cloth, the learning outcomes of fourth grade elementary school children improved. The effectiveness of using flannel cloth media to improve the learning outcomes of fourth grade elementary school children, after research was conducted at one of the elementary schools in Langkat using flannel cloth media, it was proven that the learning outcomes of fourth grade elementary school children could improve.